The constitution and the singular identity of the collective: who, 'we'?. Issue 4 (December 2018) - Nissen, Morten
Abstract Faced with problems of organizational belonging, it is necessary and relevant to approach singular collective identity: the 'who, we?' question as indexical. For this, approaches from social theory outside of the 'organization' field are employed in the analysis of three cases suggested as prototypical. First, the Narcotics Anonymous is seen to mystify its essential workings with a religious metaphor added to its appearance as a standardized civil society association. Second, a grass-roots-based collective of social youth work is viewed as struggling for recognition through a performative branding hidden behind a radically situated self-conception. Finally, a web-portal is modeled as co-authoring counseling with art and research and as reflecting itself as at once concrete and universal. This casts a new light on the issue of organizational belonging, which could be sufficiently grasped neither in the dominant functionalist approaches, nor in the systemic, institutionalist, or poststructuralist theories that oppose them.